Contribution of Eisenia andrei earthworms in pathogen reduction during vermicomposting - Procházková, Petra; Hanč, Aleš; Dvořák, Jiří; Roubalová, Radka; Drešlová, Markéta; Částková, Tereza; Šustr, Vladimír; Škanta, František; Pacheco, Natividad Isabel Navarro; Bilej, Martin (Environmental science and pollution research international, 2018)
Vermicomposting is a process of degradation of biowaste which involves complex interactions between earthworms and microorganisms. This process lacks a thermophilic stage and thus, the possible presence of pathogens poses a potential health hazard. To assess the contribution of earthworms during the selective reduction of various pathogens, apple pomace substrate was artificially inoculated with Escherichia coli, Salmonella spp., thermotolerant coliform bacteria, and Enterococci. The artificial bacterial load did not influence the weight, reproduction, or intestinal enzymatic activity of the earthworms, but it caused reversible histological changes to the epithelial layer and chloragogen tissue of their intestines. The reduction of pathogenic Enterococci and E. coli from the substrate was accelerated by earthworms (63-fold, 77-fold, and 840-fold for Enterococci and 6-fold, 36-fold, and 7-fold for E. coli inoculated substrates after 2, 4, and 6 weeks, respectively). Moreover, the rapid elimination of Salmonella spp. was supported by the upregulated expression of two pattern recognition receptors which bind lipopolysaccharide, coelomic cytolytic factor, and lipopolysaccharide-binding protein. Further, the microbiomes of the intestine and the composting substrate differed significantly. Graphical abstract.
Keywords: Immunity; Gastrointestinal Microbiome; Microbiome; Composting; kompostování; Pattern recognition receptor; střevní mikroflóra; Animals; Biowaste; Eisenia; Escherichia coli; Pathogen; Earthworm; Vermicompost; zvířata; Oligochaeta; půdní mikrobiologie; Soil Microbiology